Initial Assessment of Hydrous Thorium(IV) Solubility and Speciation in Geological Environments: An Experimental Approach in Presence of Organic Ligands - S. CETINER, ZIYA (Asian Journal of Chemistry, 2010)
Data on the hydrolysis of Thorium(IV) and solubility of ThO2 in presence of organic ligands are of critical importance to the safe disposal and treatment of high-level nuclear waste. Such data are required to predict reliably thorium behaviour in high-level waste repositories where organic anions may be present. In addition, Th(IV) is considered to be a chemical analogue of tetravalent actinides such as Pu(IV). To establish the effect of pH and organic ligands on the hydrolysis of Th(IV), experiments on the solubility of hydrous ThO2 in aqueous solution at room temperature were performed, covering a wide range of pH (pH = 3-12) in 0.1 molal NaNO3 solutions. Experiments also were conducted in the presence of citrate, oxalate and EDTA with a concentration range of 100-500 μmol. The solubility of ThO2 decreases with increase of pH (pH 3 to 6) and remains near the detection limit of ICP-MS (10-9-10-10 M) in the range pH 6-12. These values are in accordance with data in the literature. The solubility of ThO2 does not appear to be a sensitive function of the concentration of the investigated organic ligands at any given pH providing the fact that bulk of organic ligands is potentially absorbed by ThO2 solid phase. Thorium concentrations obtained from unfiltered and filtered samples showed almost an order of magnitude variation in molal concentration indicating a significant amount of colloid formation.